A donor risk index for graft loss in pediatric living donor kidney transplantation. Issue 10 (9th April 2019) - Wasik, Heather L.; Pruette, Cozumel S.; Ruebner, Rebecca L.; McAdams-DeMarco, Mara A.; Zhou, Sheng; Neu, Alicia M.; Segev, Dorry L.; Massie, Allan B.
Abstract : Pediatric kidney transplant candidates often have multiple potential living donors (LDs); no evidence‐based tool exists to compare potential LDs, or to decide between marginal LDs and deceased donor (DD) kidney transplantation (KT). We developed a pediatric living kidney donor profile index (P‐LKDPI) on the same scale as the DD KDPI by using Cox regression to model the risk of all‐cause graft loss as a function of living donor characteristics and DD KDPI. HLA‐B mismatch (adjusted hazard ratio [aHR] per mismatch = 1.04 1.271.55 ), HLA‐DR mismatch (aHR per mismatch = 1.02 1.231.49 ), ABO incompatibility (aHR = 1.20 3.268.81 ), donor systolic blood pressure (aHR per 10 mm Hg = 1.01 1.071.18 ), and donor estimated GFR (eGFR; aHR per 10 mL/min/1.73 m 2 = 0.88 0.940.99 ) were associated with graft loss after LDKT. Median (interquartile range [IQR]) P‐LKDPI was −25 (−56 to 12). 68% of donors had P‐LKDPI <0 (less risk than any DD kidney) and 25% of donors had P‐LKDPI >14 (more risk than median DD kidney among pediatric KT recipients during the study period). Strata of LDKT recipients of kidneys with higher P‐LKDPI had a higher cumulative incidence of graft loss (39% at 10 years for P‐LDKPI ≥20, 28% for 20> P‐LKDPI ≥−20, 23% for −20 > P‐LKDPI ≥−60, 19% for P‐LKDPI <−60 [log rank P  < .001]). The P‐LKDPI can aid in organ selection for pediatric KT recipients by allowing comparison of potential LD and DD kidneys. Abstract : The authors propose a risk index for pediatric living donor kidney transplantation, which quantifies the risk of graft loss based on living donor characteristics on the same scale as the Kidney Profile Donor Index.